(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Alpha galactosidase A (GLA) deficiency causes Fabry disease (FD), an X-linked lysosomal storage disorder. Multiple organ involvement occurs in affected males and, to a lesser extent, in affected females due to the progressive, intralysosomal buildup of neutral glycosphingolipids in endothelial cells and podocytes. GLA analysis in leukocytes or dried blood spots (DBS) is used to diagnose FD in males, but GLA activity in females may be within the normal range. The usual enzymology fluorometric approach applied to dried blood spots made this achievable. High-throughput multiplexable tests were then created, including tandem mass spectrometry and digital microfluidics. Some nations have recently started using DNA-based techniques for newborn screening. Numerous newborn screening pilot projects and initiatives have been put into place globally using these techniques. However, there are still a number of issues, and not everyone agrees that newborns should be screened for Fabry disease. Specifically, a significant number of afflicted females are missed by enzyme-based approaches. High-throughput screening of at-risk groups and neonates has been made easier with the introduction of fluorometric and mass spectrometry techniques for enzyme analysis in DBS. However, genetic investigation of the GLA gene continues to be the primary diagnostic method for FD females. Furthermore, a significant percentage of babies have variations of unknown significance or later onset types, which raise ethical concerns. Long-term monitoring of those identified through birth screening will advance our understanding of the illness’s natural course, phenotypic prediction, and patient care, enabling a more accurate assessment of the advantages and disadvantages of newborn Fabry disease screening. The comprehensive analytical procedure for measuring GLA activity in DBS using tandem mass spectrometry will be provided in the next unit.